Aerodynamics of horizontal axis wind turbines - Graham,J (John Wiley & Sons, 2021)
These are complemented by new sections on blade add-ons and noise in the aerodynamics chapters, which now also include a description of the Leishman-Beddoes dynamic stall model and an extended introduction to Computational Fluid Dynamics ...